Factors Related to The Incidence of Pneumonia in Toddlers at Karangrejo Metro Utara Community Health Center - Meirawati, Diah; Priyani, Titin (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2024)
Introduction: According to the World Health Organization (WHO), pneumonia accounted for 16% of deaths among children under five worldwide, with a total of 920,136 deaths in 2021. The Metro City Health Office (2021) recorded the highest prevalence was found at Karangrejo Public Health Center, with 288 out of 677 children affected (65.1%). Objective: This study aims to identify the factors associated with the incidence of pneumonia in children under five at Karangrejo Public Health Center, North Metro. Method: The type of research used is analytical with a case-control approach. The dependent variable is pneumonia, and the independent variables in this study are low birth weight, age of the child, and immunization status. The research sample consists of 36 pneumonia cases and 36 control respondents among children under five at Karangrejo Public Health Center, selected using systematic random sampling. Data collection was carried out using questionnaires, and statistical analysis was performed using the chi-square test. Results: Based on the study, it was found that 45.8% of children under five with low birth weight were at risk, 48.6% of children were at risk due to age, and 54.2% were at risk due to immunization status. The bivariate analysis showed a significant relationship between low birth weight and the incidence of pneumonia (p-value = 0.000), a significant relationship between the age of the child and the incidence of pneumonia (p-value = 0.000), and a significant relationship between immunization status and the incidence of pneumonia (p-value = 0.000). Conclusion: Low birth weight, age of the child, and immunization status are associated with the incidence of pneumonia in children under five. The researcher provided counseling regarding the various factors that can contribute to the occurrence of pneumonia in young children.